Heat transfer optimization of MWCNT-Al2O3 hybrid nanofluids under convective and irreversible effects - Yusuf, Abdulhakeem; Khan, Sami Ullah; Hassan, Mohsan; Bhatti, M.M.; Öztop, Hakan Fehmi (Springer, 2025)
Effective thermal management in automotive radiator systems is crucial for enhancing engine performance and energy efficiency. Traditional coolants often fall short in achieving the desired heat transfer rates, prompting the use of advanced working fluids such as hybrid nanofluids. Among these, hybrid mixtures containing Multi-Walled Carbon Nanotubes (MWCNTs) and Aluminum Oxide (Al2O3) nanoparticles in water (H2O) have shown promise due to their complementary thermal and stability characteristics. However, most existing studies focus either on experimental heat transfer enhancement or simplified theoretical modeling, often neglecting thermodynamic irreversibilities and practical effects such as velocity slip, thermal radiation, and internal heat generation. This study addresses these limitations by performing a theoretical analysis of boundary layer flow in a MWCNT-Al2O3/H2O hybrid nanofluid, considering all relevant physical phenomena affecting thermal transport in radiator systems. The governing momentum, energy, and entropy equations are formulated using a non-similar transformation and solved numerically via the Galerkin Weighted Residual Method (GWRM). Validation against previously published data confirms the accuracy of the results. It is found that increasing the nanoparticle volume fraction (to) significantly enhances the Nusselt number while reducing entropy generation, thus improving both heat transfer and thermodynamic efficiency. The findings align with experimental literature and offer useful design insights for next-generation automotive cooling systems. © The Author(s) 2025.
Keywords: Automobile radiator; Entropy generation; Hybrid nanofluid; MWCNTs-Al2O3/H2O; Radiator coolant